Perilaku Masyarakat Terhadap Kesehatan Lingkungan (Studi di Pantai Desa Ketong Kecamatan Balaesang Tanjung Kabupaten Donggala) - Sri Wahyuni; Kaharuddin Nawing (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
The purpose of this study is description people's behavior, identify the factors that influence people's behavior, and identify the policy that is applied for environmental health in the beach Village of Ketong Kecamatan Balaesang Tanjung Kabupaten Donggala. The type of research used in this research is qualitative research with a case study approach. Data analysis techniques include data reduction data presentation, and conclusion. The results showed 1) the Behavior of the public against the health of the environment focused on two indicators of environmental health and the provision of facilities of family latrines. The behavior of the villagers Ketong in the garbage disposal is still relatively less, the provision of latrine facilities family, the government had taken action by making family latrines are common. (2) the Factors that affect the behavior of the public against the health of the environment there are three, namely, public awareness of environmental health is still relatively low, people's understanding of the health of the environment that is already understood the society and habits of society that are difficult to be changed, and the provision of means of hygiene which is relatively less and far from adequate. (3) Policies related to the health of the environment are still the planning process that is applied in 2021. The policy is creating trash in every household, making LANDFILL, recycling, and making family latrines to the public (5-10 KK) in one environment.